The Muslim Brotherhood and Egypt's succession crisis: the politics of liberalisation and reform in the Middle East - Zahid, Mohammed (Library of modern Middle-East studies, 2010)
Framing economic and political reform in the Middle East -- Shifting sands : the Middle East between authoritarianism and democratisation -- Economic and political reform in Egypt after 1991 -- The Muslim Brotherhood in Egypt : growth and development, 1928-1975 -- The Muslim Brotherhood : the transition from piety to politics -- The art of politics : the new MB generation, the syndicates and power -- The politics of succession in Egypt -- Continuity and discontinuity in economic and political reform in Egypt